2022
DOI: 10.1108/itp-11-2020-0786
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of actual business intelligence technology use: an individual user perspective

Abstract: PurposeAlthough much is understood about Business Intelligence (BI) technology adoption, less is known about the complementary organisational resources that drive the actual use of BI systems and the impacts of BI systems at an individual employee level. This study aims to develop and test a model of the impact of key complementary organisational resources on employees' actual BI systems’ use behaviours and their decision-making performance.Design/methodology/approachTo test the research model, a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, past research has suggested that many organizations reap little or no benefit from the BIS implementation (Torres et al , 2018; Trieu, 2022; Nuseir, 2021). Hence, organizations are in a continuous struggle to find the best way to leverage value from BIS and to make their implementation successful and efficient.…”
Section: Literature and Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, past research has suggested that many organizations reap little or no benefit from the BIS implementation (Torres et al , 2018; Trieu, 2022; Nuseir, 2021). Hence, organizations are in a continuous struggle to find the best way to leverage value from BIS and to make their implementation successful and efficient.…”
Section: Literature and Theoretical Foundationsmentioning
confidence: 99%
“…Previous studies have found that 70 to 85% of BIS projects fail to yield the expected returns (Trieu, 2022; Ain et al , 2019). In emerging economies, Ahmad et al (2021) estimated a failure rate of about 80% due to both technological and managerial issues.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several organizations have not achieved the appropriate and probable benefits from BI investments. The estimated rate of BI projects failing to yield the expected returns ranges from 70 to 85% (Trieu, 2022; Nuseir, 2021; Ain et al , 2019). Gartner Inc. Statistics for 2020 have shown that between 70 and 80% of BI technology projects result in failure.…”
Section: Introductionmentioning
confidence: 99%